1999
DOI: 10.1037/0012-1649.35.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Quick, automatic, and general activation of orthographic and phonological representations in young readers.

Abstract: Second through 6th graders were presented with nonword primes (orthographic, pseudohomophone, and control) and target words displayed for durations (30 and 60 ms) that were brief enough to prevent complete processing. Word reading skills were assessed by 3 word and nonword naming tasks. Good readers exhibited more orthographic priming than poor readers at both durations and more pseudohomophone priming at the short duration only. This suggests that good readers activate letter and phonemic information more eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
90
3
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 56 publications
10
90
3
4
Order By: Relevance
“…It is interesting to contrast this with the phonological findings from Experiment 3, where the cross-language congruency effect of the grapheme-to-phoneme correspondences was only observed for those participants with the longest exposure to the L2. Although one could argue that the adolescent groups did not activate phonological information during the letter detection task (see though Booth, Perfetti & MacWhinney, 1999) for quick phonological activation in monolingual word recognition), it seems equally possible that accurate grapheme-to-phoneme correspondences within the L2 take some time to be established and that incorrect decoding of the L2 words might explain the non-significant findings in the adolescent groups. Future studies on grapheme coding would probably benefit from assessing learners' reading skills in L2 as well as orthographic (i.e.…”
Section: Discussionmentioning
confidence: 98%
“…It is interesting to contrast this with the phonological findings from Experiment 3, where the cross-language congruency effect of the grapheme-to-phoneme correspondences was only observed for those participants with the longest exposure to the L2. Although one could argue that the adolescent groups did not activate phonological information during the letter detection task (see though Booth, Perfetti & MacWhinney, 1999) for quick phonological activation in monolingual word recognition), it seems equally possible that accurate grapheme-to-phoneme correspondences within the L2 take some time to be established and that incorrect decoding of the L2 words might explain the non-significant findings in the adolescent groups. Future studies on grapheme coding would probably benefit from assessing learners' reading skills in L2 as well as orthographic (i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, phonological and orthographic representations become closely linked during reading acquisition. Behavioral and computational modeling research has shown that phonological and orthographic processes are more interactive in skilled versus less skilled readers (Booth, et al 1999;Plaut and Booth 2000). However, the neural mechanisms that underlie interactions between phonological and orthographic processes are not clearly understood.…”
Section: Introductionmentioning
confidence: 99%
“…A spelling task to auditorily presented words requires the maintenance of phonological information in memory, accessing visual orthographic information, segmentation of the onset from the rime, and a determination of whether two words have similar spelling of the rime. A spelling task presented in the visual modality could be based on visual orthographic information, however, it is likely that children would activate phonological representations because of behavioral studies showing automatic activation of phonological representations when reading (Booth et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Because our spelling tasks demanded access to orthographic representations and studies have shown age-related effects in fusiform gyrus when reading (Booth et al, 2003b(Booth et al, , 2001, we may expect developmental increases in the influence from these primary cortical regions on left fusiform gyrus. However, behavioral studies suggests that there are developmental increases in the automatic activation of phonological information (Booth et al, 1999), so alternatively we may expect age-related increases in the influence from these primary regions on areas involved in phonological processing (i.e. left dorsal inferior frontal gyrus and left superior temporal gyrus) despite the orthographic requirements of the task.…”
Section: Introductionmentioning
confidence: 99%